DIVERSIFIKASI OLAHAN PANGAN BERBASIS IKAN UNTUK MENDUKUNG DESA PANCASAN KECAMATAN AJIBARANG SEBAGAI DESA EDUWISATA - Hastuti, Dewi Wisudyanti Budi; Hidayati, Nuning Vita; Riviani, Riviani; Pujihastuti, Etin (Universitas Mataram, 2024)
Pancasan Village is a village with the theme of Circular Economy Based Edutourism. Pancasan Village is a village located in Ajibarang District, Banyumas Regency, Central Java Province. There are two groups of Fish Farmers (Pokdakan)